Graphene Oxide-Paraffin as Working Electrode for Cyclic Voltammetry Analysis for Cadmium(II) - Setiarso, Pirim; Hidayatulloh, Taufik (Asian Journal of Chemistry, 2019)
In this work, the composition ratio of graphene oxide-paraffin as the best working electrode for analysis of cadmium solution at optimum conditions using cyclic voltammetry is reported. Graphene oxide from graphite was synthesized and characterized using the improved Hummer method. Testing the composition and condition of graphene oxide:paraffin electrode is best done by manipulating the graphene oxide:paraffin ratio, pH, deposition time and scan rate. The composition with a ratio of 8:2 % of graphene oxide:paraffin electrode produces the best of voltammogram. Recovery analysis is also performed with the results of linear curves in cadmium(II) solution with linearity 0.98992. Cyclic voltammetry analysis using graphene oxide:paraffin electrodes at optimum pH resulted an average recovery of 97.64 %.